Career Management Peculiarities in Educational Institutions - Paresashvili, Nino; Giorgobani; Nikvashvili, Maia; Pirtskhalaishvili, Dea; Kharadze, Natalia (European Journal of Economics and Business Studies, 2019)
Education is the most important component of career planning. Proper education allows the individual to have a strong foundation for a future successful career. It is interesting what are the peculiarities of career management in education field? Thus, our article deals with a comparative analysis between the education field, of career management and the public sector and private sector employers.We have formulated the following hypotheses: Hypothesis HP1: Have you ever participated in qualification raising courses with the help of the organization (without or with financing) that were related specifically to your work to perform? (Q)7 affects the forms of raising qualifications by the respondents – as an individual and as a group (Q8), also whether they were promoted after upgrading the qualification (Q9); Hypothesis HP2: (Q13) Vertical and horizontal career growth of employees affects a respondent’s career movements inside and outside the organization (Q14)Hypothesis HP3: Employment Field Q1 affects Have you heard whether your colleague’s career is moving forward with the help of other influential people? Q23. In educational institutions, the peculiarities of career growth have been highlighted, such as a high number of employees who were accepted at work by means of a job contest, lower expectations of career growth, which have reduced the desire to be employed in the field of education. The promotion of employees is not always objective, raising professional qualifications is not accompanied by work and career promotion and increase in wages. Our conclusions and recommendations will have a beneficial impact on improving the education sphere.